Preventing dynamic rollover in brownout - Gatter, A. (My University, 2019)
The Institute of Flight Systems at the DLR (German Aerospace Center) site in Braunschweig, Germany is trying to find ways to improve the safety of helicopter operations. One very dangerous type of operation that is the landing of a helicopter. Loss of situational awareness can lead to unwanted contact with objects or a dynamic rollover when touching the ground. This paper presents research with optical navigation methods that has been conducted towards minimizing the danger of a dynamic rollover in bad visual conditions. Optical navigation is a method that is often used for navigating small unmanned aircraft. However, the so far conducted research in that field usually focuses on undegraded visual environment. Most of the optical navigation methods are designed to work with images that can fully be evaluated. In this paper, a set of existing optical navigation methods is tested towards the ability to work in degraded visual environment. Further, a self-developed method is presented that has been designed to be abe to work in scenarios where most parts of an image cannot be evaluated. The methods are tested on recorded flight test data. These flight test data are modified with a set of masks that simulate a visibility impairment. The conducted tests show that existing optical navigation methods do struggle when the complete image area cannot be evaluated. The evaluation of the self-developed method shows that it is not affected by impaired sight. However, its performance in situations with non-restricted sight shows to be behind the performance of some of the existing methods.